Social Media Research: A Narrative Review - Markus Kick (Springer Gabler, 2015)
Even though the technological developments of web 2.0 and social media opened up a multitude of possibilities for companies to communicate with their customers, marketers, to a certain extent, lost direct control of their brands. Users are able to exchange opinions about companies, products, services, or brands independent of corporate influences at high speed and almost no cost. Marketing research has quickly picked up the new technological developments, generating enormous numbers of studies. However, the findings are highly diverse and confusing at the same time. This paper provides a systematic overview of top-tier social media research. A main emphasis is put on empirical studies that investigate the effects of user-generated content on measurable corporate performance indicators. A total of 102 articles are used as input for the conducted qualitative meta-analysis. Findings are sorted along the proposed framework of the “social media value chain”. The analysis encompasses effects of electronic word-of-mouth on corporate consumer mindset metrics, product and market performance indicators, and financial performance measures. The analysis extracts the inherent moderators of electronic word-of-mouth-effects and provides a suitable framework for discussion. In addition, the dual role of companies as moderators of ongoing social media communication and content creators within viral marketing campaigns is also dissected. Social media conversations are a powerful force that shows effect along the whole value chain. Pure volume measures show the strongest effect. Even though valence measures contain a high degree of information, inconsistent results can be observed depending on valence operationalization and empirical methods used. Research needs to develop a better and deeper understanding of valence measures. Further, experimental field studies provide a good starting point for future empirical work. The multitude of moderator effects reveals that the impact of electronic word-of-mouth is not generalizable across industries, product categories, and social media platforms. However, social media conversations contain rich information that has to be utilized by the marketing profession.
Additional information: Reworking paper for a practitioners target audience. Cf. Kick M. (2015): Selected Essays on Corporate Reputation and Social Media. Springer Gabler, Wiesbaden, https://doi.org/10.1007/978-3-658-08837-8
Keywords: 330